TA'LIM AL-LUGHAH AL-'ARABIYAH LI AL-NATHIQIN BI GHAIRIHA BI AL-THARIQAH ALATI IKTASABUHA MIN LUGHATIHIM AL-UM - Muhammad, Abdalla Shobak (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The primary goal of language teaching is to enable students to understand the proper and clear language expression that he listens, or reads, or writes; in order to achieve a very lofty goal namely communication between human beings. It is recommended that we start teaching Arabic language to children since their early age. It is that a child spends hundreds and perhaps thousands of hours listening to his mother tongue, to recognize their voices, and to distinguish between them and finally to produce words and sentences. This is what we understand about early stages of Arabic language learning. DOI: 10.15408/a.v1i2.1144